Cloning and Characterization of the Gene Encoding the Heat Shock Protein HSP83 from Trypanosoma cruzi - Fernández, Ana (2024)
[Objective] Trypanosoma cruzi, a causal agent of Chagas’ disease, is a parasite whose life cycle alternates between an invertebrate (triatomine) and a vertebrate (mammal) host. Various studies have shown that in T. cruzi, HSP83 (a homolog of HSP90) is essential for cell division and control of the response to thermal stress. This investigation focused on studying the cloning, bioinformatic characterization, and expression of the heat shock protein HSP83 T. cruzi gene for further cell signaling studies. [Methodology] RNA was extracted from T. cruzi epimastigotes (EPm6 clone, MHOM/VE/2007/ 6c) using a commercial kit. The cDNA encoding HSP83 was determined using RT-PCR on extracted mRNA, for which the primers were designed based on the HSP83 sequence of T. cruzi strain CL Brener. Cloning was performed using pGEM®T-Easy and subcloned into the expression vector pQE30. Sequence and bioinformatic characterization were performed. The gene was expressed, and the recombinant protein was purified using affinity chromatography and identified through immunoblotting. [Results] Sequence analysis showed similarity to the gene encoding HSP83 from Trypanosoma cruzi, and HSP domains and B epitopes in the sequence were also observed. After 3 hours of induction with IPTG, a recombinant protein with an approximate weight of 83 kDa was obtained. The immunoblotting reaction with hyperimmune anti-T. cruzi epimastigote serum helped detect a single band with a molecular weight of nearly 83 kDa. [Conclusions] All results indicate that the cloning and characterization of HSP83 from Trypanosoma cruzi was achieved.